Pengaruh Pelatihan dan Kompetensi Terhadap Kinerja Pegawai Badan Perencanaan Pembangunan Daerah (BAPPEDA) - Ramadhani, Pila; Hasni, Hasni; Alprida, Alprida; S, Syahri Ramadahan; Dinsar, Arfandy (Jurnal Ilmiah Multidisiplin Amsir, 2023)
The importance of competence in performance management is also reflected in relation to individual behavior. Performance management not only involves technical aspects, but also how individuals demonstrate behavior that supports goal achievement. By understanding the complexity of the role of HR, especially civil servants at BAPPEDA Sidrap, this research aims to explore the relationship between work performance assessment, training, and competency development as the main factors in improving performance. Quantitative data, namely data obtained in the form of numbers that relate to the problems discussed in this research can be calculated such as income values ​​and other data that can support the discussion. Qualitative data, namely data obtained through a list of statements (questionnaires) from selected respondents and information related to the problems discussed in this research. The research results support that the training variable (X1) positively and significantly affects performance. This is shown in the Regression Coefficient X1 value of 0.397 which states that every 1 unit increase in training will increase training by 0.397 units. A probability value that is smaller than 5%, namely 0.000 0.05, indicates that training has a positive effect on performance. Training (X1) and Competency (X2) have a positive effect on the performance (Y) of employees at the Sidenreng Rappang Regency Bappeda Office. Statistical analysis shows a significance (Sig) of 0.05 and Fcount Ftable. Partially, Training (X1) and Competency (X2) also have a significant effect, with a Sig value of 0.05 and t count t table.